2008
DOI: 10.1021/ma801476e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) Grafting in Miniemulsion Polymerization

Abstract: Poly(vinyl alcohol) (PVOH) can be advantageously used in miniemulsion polymerization as it yields latexes more stable than those produced by conventional emulsion polymerization. Latex stabilization and properties are affected by the extent of grafting of PVOH. The effect of the initiator system and the polymerization process (miniemulsion vs conventional emulsion polymerization) on the extent of grafting of PVOH in the polymerization of vinyl acetate and Veova10 was studied. It was found that the fate of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…The latex is stabilized by adsorbed and grafted PVA in the present work. The PVA adsorbs on the latex surface with the hydrophobic acrylate units providing the anchoring segments and the hydrophilic hydroxyl units being soluble in the aqueous phase as stabilizing moieties [18,19]. While, the grafting occurs by hydrogen abstraction at the methane carbons of the PVA followed by propagation of monomer.…”
Section: Introductionmentioning
confidence: 99%
“…The latex is stabilized by adsorbed and grafted PVA in the present work. The PVA adsorbs on the latex surface with the hydrophobic acrylate units providing the anchoring segments and the hydrophilic hydroxyl units being soluble in the aqueous phase as stabilizing moieties [18,19]. While, the grafting occurs by hydrogen abstraction at the methane carbons of the PVA followed by propagation of monomer.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In addition, chain transfer to the PVOH led to graft copolymers. [25][26][27] The analysis of these polymers using the conventional Soxhlet extraction with THF led to the conclusion that gel is formed in this reaction. However, it has been recently demonstrated that this is an artifact of the method due to the insolubility of the PVOH containing graft copolymers in THF.…”
Section: Switching Production Of Branches Polymers From Semicontinuoumentioning
confidence: 99%
“…This mechanism was in accordance with the fundamentals of methods to improve the stability of PVA/MMA emulsions, such as modifying PVA with a thiol-terminated group [6,23,24] or the addition of alcohol such as methanol [10][11][12], which repressed the grafting reaction through chain transfer and allowed more PVA molecules to distribute on the surfaces. Moreover, it was understandable that the mini-emulsion polymerization of MMA monomers stabilized by PVA could carry out smoothly because the PVA molecules all located on the O/W interfaces and there existed no problem of inside grafting [13,14].…”
Section: Factors Influencing Colloidal Stability Of the Final Emulsionsmentioning
confidence: 99%
“…Some assumed this arose from the poor grafting ability of conjugated monomers such as acrylates and methacrylates [4][5][6], while excessive grafting of the soluble polymers was believed to be the influencing factor by others [7,8]. Relevant results have been reported that quite a large quantity of PVA was grafted in the polymerizations of n-butyl acrylate and methyl methacrylate monomers [9,10] and it was feasible to get stable emulsions by suppression of grafting [10][11][12][13][14], but the reason for the unstability of relevant colloids was not given and still indistinct.…”
Section: Introductionmentioning
confidence: 99%